Probing the ionic structure of FLiNaK–ZrF4 salt mixtures by solid-state NMR. Issue 39 (6th July 2021) - Lan, Rongshan; Liu, Yiyang; Han, Ling; Yang, Jing; Yin, Huiqin; Ge, Min; Fu, Xiaobin; Liu, Hongtao; Qian, Yuan
Abstract : The evolution of the [Zr x F y ] 4 x − y ionic structures in FLiNaK–ZrF4 salt mixtures was elucidated through solid-state NMR techniques when the melt salts were being solidified. Abstract : In this study, by applying 19 F, 23 Na and 7 Li high-resolution NMR methods, the evolution of the [Zr x F y ] 4 x − y local ionic structures in FLiNaK–ZrF4 salt mixtures were elucidated. K3 ZrF7, Na3 ZrF7 and Na7 Zr6 F31 crystal phases were identified when the melt salts were being solidified. The distribution of these [Zr x F y ] 4 x − y species was dependent on the content of ZrF4 in FLiNaK eutectic salts. Moreover, K3 ZrF7 phase transition from an orthorhombic lattice into a disordered cubic lattice was clarified, thereby causing dynamics of the coordinated F − ions to be reduced and the well-ordered crystal lattices to be destroyed. These mentioned results provide a further insight into the Zr–F based ionic structure and the formation of the disordered Zr–F structure in ZrF4 -based eutectic salts.